2018
DOI: 10.1001/jamainternmed.2018.0411
|View full text |Cite|
|
Sign up to set email alerts
|

Dialysis Initiation and Mortality Among Older Veterans With Kidney Failure Treated in Medicare vs the Department of Veterans Affairs

Abstract: The benefits of maintenance dialysis for older adults with end-stage renal disease (ESRD) are uncertain. Whether the setting of pre-ESRD nephrology care influences initiation of dialysis and mortality is not known.OBJECTIVE To compare initiation of dialysis and mortality among older veterans with incident kidney failure who received pre-ESRD nephrology care in fee-for-service Medicare vs the Department of Veterans Affairs (VA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…Financial incentives and the pressure to meet productivity goals drive overutilisation of unnecessary testing and treatment, limit time with the patient and move the focus towards technical testing. This phenomenon is not limited to cardiology; evidence for variation in care attributable to differences in reimbursement mechanisms and supplier-induced demand exist for many specialties within healthcare including surgery,26 nephrology,27 neonatology28 and obstetrics 29. Published studies in diverse health settings in countries aside from the USA28 30 suggest that financial incentives lead to similar practice patterns by physicians in diverse settings and have a central role in efforts to change practice.…”
Section: Discussionmentioning
confidence: 99%
“…Financial incentives and the pressure to meet productivity goals drive overutilisation of unnecessary testing and treatment, limit time with the patient and move the focus towards technical testing. This phenomenon is not limited to cardiology; evidence for variation in care attributable to differences in reimbursement mechanisms and supplier-induced demand exist for many specialties within healthcare including surgery,26 nephrology,27 neonatology28 and obstetrics 29. Published studies in diverse health settings in countries aside from the USA28 30 suggest that financial incentives lead to similar practice patterns by physicians in diverse settings and have a central role in efforts to change practice.…”
Section: Discussionmentioning
confidence: 99%
“…When nephroangiosclerosis and diabetes-rather than pyelonephritis and glomerulonephritiscame to be seen as the causes of end-stage renal disease (ESRD), this was not without consequences for dialysis tolerance, and the first caveats on eating during dialysis date to this phase. The progressive shortening of dialysis time, made possible by increased dialysis efficiency, occurred at the same time as the dialysis population started to become progressively older, a process that is continuing, at least in many European settings [57][58][59][60][61][62].…”
Section: Intradialytic Nutrition: a Bit Of Historymentioning
confidence: 99%
“…But despite being less likely to start dialysis, the VA patients’ mortality rate was 9% lower. 26 Another recent study found that patient satisfaction was markedly lower in investor-owned clinics than in nonprofit facilities. 27…”
Section: Corporate Medicine and For-profit Carementioning
confidence: 99%